Perencanaan Pajak Dalam Rangka Penghematan Pembayaran Pajak Terutang Studi Kasus pada PT GL HI-TECH INDONESIA - Dian Pernanda; Arniati Arniati (Politeknik Negeri Batam, 2013)
The purpose of tax planning is not to implement fraud in tax obligation, but to use opportunity regarding tax regulation which can give benefit to company and not affecting loss government legally. This research is done to make tax planning in order to reduce tax payable of PT GL HI-TECH INDONESIA. The efforts that can be done to implement tax planning to minimize company tax payable (PPh) are by reduce undetectable expenses, increase deductible expenses, selecting accounting method and purchase asset with leasing. Researcher use interview method, documentation and observation to get information/data accurately form the company. The result of research show that the tax planning that can be implemented in PT GL HI-TECH INDONESIA are by increase expectable income by doing postpone of income, increase material service expenses by recording in advance, prepare normative list of entertain expenses, maximize repair maintenance expenses by using vehicle 100% for company operational, selecting depreciation method by using double declining and purchase asset with leasing.